How trust towards green textile brands and green altruism affect green brand loyalty: the mediation role of green purchse intention - AYSUNA TÜRKYILMAZ, CEYDA (My University, 2021)
Sustainable activities have gained importance all over the world with the effects of problems such as increasing population, industrialization, and depletion of resources. In the literature, the contribution of sustainable products to green purchasing intention and their effect on brand loyalty have been examined. Consumers' perception of sustainable initiatives is positive, and their contribution to trust and purchase intention has been shown. However, although there are many studies on sustainability in the literature, the effects of green altruism and trust in the textile sector on green purchase intention an green brand loyalty have not been examined. This study examined how sustainable products in the textile sector affect the consumer's sense of trust and altruism and how these variables contribute to green purchase intention and green brand loyalty. In this regard, this paper aims to contribute to the gap in the sustainability literature by proposing a different point of view. Analysis of the data collected by an online survey may shed light on the marketing activities of the managers in the textile sector, highlighting the importance of brand loyalty towards sustainable products and how this loyalty can be created. In addition, this study will also have a social impact, by raising awareness of depleted resources and attracting consumers' interest in sustainable products.

Sürdürülebilir faaliyetler, artan nüfus, sanayileşme, kaynakların tükenmesi gibi sorunların etkisiyle tüm dünyada önem kazanmıştır. Literatürde sürdürülebilir ürünlerin yeşil satın alma niyetine katkısı ve marka sadakati üzerindeki etkisi incelenmiştir. Tüketicilerin sürdürülebilir inisiyatif algısı olumlu olup, güvene ve satın alma niyetine katkıları gösterilmiştir. Ancak literatürde sürdürülebilirlik ile ilgili birçok çalışma olmasına rağmen yeşil özgecilik ve tekstil sektöründe yeşil satın alma niyetine güven ve yeşil marka sadakati incelenmemiştir. Bu çalışma, tekstil sektöründeki sürdürülebilir ürünlerin tüketicinin güven ve fedakarlık duygusunu nasıl etkilediğini ve bu değişkenlerin yeşil satın alma niyetine ve yeşil marka sadakatine nasıl katkıda bulunduğunu incelemiştir. Bu bağlamda, bu makale farklı bir bakış açısı önererek sürdürülebilirlik literatüründeki boşluğa katkıda bulunmayı amaçlamaktadır. Çevrimiçi bir anket ile toplanan verilerin analizi, tekstil sektöründeki yöneticilerin pazarlama faaliyetlerine ışık tutarak, sürdürülebilir ürünlere yönelik marka sadakatinin önemini ve bu sadakatin nasıl oluşturulabileceğini vurgulayabilir.Ayrıca çalışmamız, tükenen kaynaklar konusunda farkındalık yaratarak ve tüketicilerin sürdürülebilir ürünlere olan ilgisini çekerek sosyal bir etkiye de sahip olacaktır.
Keywords: Sosyal ve Beşeri Bilimler; Social Sciences and Humanities; Sosyal Bilimler (SOC); Social Sciences (SOC); Sürdürülebilirlik; Yeşil Ürünler; Yeşil Marka Sadakati; Fedakarlık; Yeşil Satın Alma Niyeti; Güven; Sustainability; Green Products; Green Brand Loyalty; Altruism; Green Purchase Intention and Trust.